ANALISIS REVEGETASI PADA LAHAN REKLAMASI TAMBANG BATU KAPUR DISPOSAL 4 DI PT SEMEN BATURAJA Tbk - Randu Ramadhanu; Ridho Yovanda; Rodiyah Nursani (Jurnal Humaniora & Sosial Sains, 2025)
PT Semen Baturaja Tbk carries out limestone mining activities using open pit methods that can cause environmental damage, especially to the structure and function of the soil. To reduce these negative impacts, post-mining reclamation activities are carried out through revegetation methods to restore the ecological conditions of the land. This study aims to analyze suitable plant species and evaluate the success rate of revegetation on Disposal 4 reclamation land with a planting year of 2020. The methods used include identifying plant species, measuring diameter, height and plant health, and quantitative analysis based on success indicators according to Permenhut P.60 / Menhut-II / 2009. From the research that has been conducted, it was found that the main use of plants is centered on sengon (Albizia chinensis) and tamarind (Tamarindus indica). The evaluation results show that the success of revegetation is quite good, indicated by the number of plants per hectare that meet minimum standards and a plant health level exceeding 80%. This study emphasizes the importance of selecting adaptive plant species and implementing appropriate maintenance in supporting the success of post-mining land reclamation.